Regional cultures, economies, and creativity
1 online resource (xvii, 296 pages).
Keywords: "Drawing on Australian and comparative case studies, this volume reconceptualizes non-metropolitan creative economies through the 'qualities of place'. This book examines the agricultural and gastronomic cultures surrounding 'native' foods, coastal sculpture festivals, universities and regional communities, wine in regional Australia and Canada, the creative systems of the Hunter Valley, musicians in 'outback' settings, Fab Labs as alternatives to clusters, cinema and the cultivation of 'authentic' landscapes, and tensions between the 'representational' and 'non-representational' in the cultural economies of the Blue Mountains. What emerges is a picture of rural and regional places as more than the 'other' of metropolitan creative cities. Place itself is shown to embody affordances, unique institutional structures and the invisible threads that 'hold communities together'. If, in the wake of the publication of Florida's Rise of the Creative Class, creative industries models tended to emphasize 'big cities' and the spatial-cum-cultural imaginaries of the 'Global North', recent research and policy discourses - especially, in the Australian context - have paid greater attention to 'small cities', rural and remote creativity. This collection will be of interest to scholars, students and practitioners in creative industries, urban and regional studies, sociology, geography, and cultural planning"--